ESTUDIO PARA LA ELABORACION DE UN MANUAL DE FUNCIONES PARA EL PERSONAL ADMINISTRATIVO, QUE LABORA EN LA UNIVERSIDAD TECNICA DE BABAHOYO, PARA MEJORAR LA CALIDAD DEL SERVICIO. - AMELIA ARAGON JARAMILLO (2011)
STUDY FOR THE PREPARATION OF A FUNCTION MANUAL FOR THE ADMINISTRATIVE STAFF WHO WORKS AT THE TECHNICAL UNIVERSITY OF BABAHOYO, TO IMPROVE THE QUALITY OF THE SERVICE.